The answer is 48 x 48 = 2304 so 2304 x 48 = 110592
Answer:
1 / x^8
Step-by-step explanation:
We know that a^b / a^c = a^ (b-c)
x^7 / x^ 15 = x^ (7-15) = x^-8
We also that that a^-b = 1/ a^b
x^-8 = 1 / x^8
Answer:
I Have noidea
Step-by-step explanation:
sorry
Answer:
(a) (5, -3)
Step-by-step explanation:
The "substitution method" for solving a system of equations requires that you write an expression that can be substituted for a variable in one or more of the other equations in the system.
<h3>Expression to substitute</h3>
The given equations are ...
We notice the first equation gives an expression for y. This is exactly what we want to substitute for y in the second equation.
<h3>Substitution</h3>
When the expression (x-8) is substituted for y in the second equation, you get ...
2x +3(x -8) = 1
This simplifies to ...
5x -24 = 1
<h3>Solution</h3>
This 2-step equation can now be solved in the usual way:
5x = 25 . . . . . . add 24 to isolate the variable term
x = 25/5 = 5 . . . . . divide by the coefficient of x
Note that we now know what the correct answer choice is.
Using the expression for y, we find ...
y = x -8 = 5 -8 = -3
The solution is (x, y) = (5, -3).
__
The attached graph confirms this solution.
6/25-63/125
Make the denominator the same:
= 30/125 - 63/125
Subtract:
= -33/125
Answer: -33/125